2017
DOI: 10.15761/pd.1000136
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans ventriculoperitoneal shunt infections: Immunocompetent preterm pediatric case series and an extensive review of literature

Abstract: Cerebrospinal fluid shunt devices are increasingly being used for decompression, and despite excellent results, obstruction and infection are concerning complications, with underlying fungal etiology a rare consideration. In this study, we focus on pediatric shunt infections caused by Candida albicans in an extensive literature review and by reporting two additional cases. Very limited information regarding diagnosis and treatment of the Candidal shunt infections is available. Prematurity and use of broad spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Similarly, Bhatti et al [ 22 ] reported on the cases of a 4-month-old female infant and a 5-month-old male infant with VP shunt-related meningitis due to azole-sensitive C. albicans . The two infants were treated with intrathecal L-amphotericin B irrigations combined with systemic therapy, without adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Bhatti et al [ 22 ] reported on the cases of a 4-month-old female infant and a 5-month-old male infant with VP shunt-related meningitis due to azole-sensitive C. albicans . The two infants were treated with intrathecal L-amphotericin B irrigations combined with systemic therapy, without adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…Limited evidence-based data are available for the optimal treatment of this rare infection. Both intravenous and intrathecal antifungal therapy have been described; however, there is a paucity of evidence to support the routine use of intrathecal/intraventricular antifungals (3,5). The Infectious Diseases Society of America (IDSA) recommends liposomal amphotericin B with or without oral flucytosine for the initial treatment of CNS candidiasis in patients outside the neonatal period (5).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal duration of treatment following device removal is not known. Case reports describe success with 3 to 6 weeks of antifungal treatment (1,3,6,7). Sterility of the CSF should be documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation